Education 3640. Problems and issues in special education. No. 04. The CELDIC Report. - Nesbit, W. C. (Wayne C.), 1943- (Teacher); Karagianis, Leslie D. (Teacher); Memorial University of Newfoundland. Division of Educational Technology (Producer)
A look at the CELDIC (Commission on Emotional and Learning Disorders In Children) report, produced in Canada in 1970 entitled One million children. "L. Karagianis, W. Nesbit" Video ends abruptly